Searching heterogeneous collections on the Web: behaviour of Excite users - Amanda Spink; Judy Bateman; Bernard. J. Jansen (Information Research: An International Electronic Journal)
As Web search services become a major source of information for a growing number of people, we need to know more about how users search heterogeneous collections using Web search engines. This paper reports the results from a major study exploring users' information searching behaviour on the EXCITE Web search engine. Three hundred and fifty-seven (357) EXCITE users responded to an interactive survey, including their search topics, intended query terms, search frequency for information on their topic, and demographic data. Results show that: users tend to employ simple search strategies, and conduct successive searches over time to find information related to a particular topic. Implications for the design of Web search services are discussed.